1996
DOI: 10.1080/07408179608966288
|View full text |Cite
|
Sign up to set email alerts
|

Joint optimization of maintenance and inventory policies for a simple system

Abstract: We examine age replacement and ordering decisions for a system with only one component subject to random failure and with room for only one spare in stock. The system incurs costs for replacement, shortage, holding, and breakage; the lead time for receipt of an ordered spare is constant. We consider the solvability and desirability of jointly optimizing these two traditionally separate decisions. We show that the problem has some convexity properties that make it amenable to minimization. For our data set, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 6 publications
0
45
0
Order By: Relevance
“…Since failure rate ( ) h x and major failure rate ( ) r x have the same monotone properties from (7), ( , ) C t T is unimodal and pseudo-convex in t and T as in Armstrong and Atkins (1996).…”
Section: Cost Modelmentioning
confidence: 93%
See 1 more Smart Citation
“…Since failure rate ( ) h x and major failure rate ( ) r x have the same monotone properties from (7), ( , ) C t T is unimodal and pseudo-convex in t and T as in Armstrong and Atkins (1996).…”
Section: Cost Modelmentioning
confidence: 93%
“…(iii) If 0 L = , t T = , 0 1 p < < , it reduces to Cleroux, Dubuc & Tilquin (1979). (iv) If 0 p = , it reduces toArmstrong & Atkins (1996).…”
mentioning
confidence: 98%
“…Then, the system is replaced by an ordered spare at failure or at preset age whichever occurs first and the optimization models regard as a decision variable. Armstrong and Atkins [17,18] extended the work of Osaki and Yamada [11] to optimize the age replacement interval and the ordering time simultaneously, and the study reported by Park and Sun [19] considered these two decision variables as well based on the work of Sheu et al [15]. To the best of our knowledge, the study of Wang et al [20] proposed firstly a joint policy of inspection-based PM and spare ordering; moreover, the optimization model is established and used for the determination of the optimal thresholds related to spare ordering, preventive replacement, and failure.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies on the joint optimization of age replacement and inventory [1,2,6], order quantity per order is assumed only one. We examine joint optimization of age replacement and spare provisioning policy which does not restrict the number of order quantity.…”
Section: Introduction †mentioning
confidence: 99%